ANALISIS FINANSIAL PADA HUTAN RAKYAT DENGAN POLA SILVOPASTURA DAN APIKULTUR DI DESA TELAGA LANGSAT KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - Anita Aulia Mulyani; Daniel Itta; Hafizianor Hafizianor (Universitas Lambung Mangkurat, 2021)
This study aims to analyze the financial and feasibility of community forests with silvopastura and apicultural patterns in the telaga langsat village, takisung district, tanah laut district. The object of this research includes farmer groups in community forests in Telaga Langsat villake. Data collected in the form of primary data and secondary data. Primary data is data that comes directly from community forest farmers, through a structured interview technique (using a questionnaire). Secondary data is data taken by collecting existing data information by requesting supporting data from the Village office and various sources or agencies. The results obtained from this study indicate that the financial analysis of community forests with the Silvopastura and Apiculture patterns is feasible to be continued and developed. The results of the calculation of the NPV, IRR and BCR values can be considered in accordance with financial. The results of the comparison of the financial feasibility study between community forest management with the Mahogany-Karet-cow silvopastura pattern produced the greatest profit value compared to the Mahogany-Karet-Honey Bee Apiculture pattern. With a value or NVP of 6,919,374,000 / ha, the BCR value of 1.11 and the IRR of 14%. Feasibility in Mahogany-Karet-Cow and Mahogany-Rubber-Honey Bee Community Forest using the Benefit Cost Ratio (BCR), it appears that the Mahogany-Karet-Cow silvopastura pattern and Mahogany-Rubber-Honey Bee apiculture are feasible and can be continued. The Mahogany-Rubber-Cow business gets BCR> 1 results and the Honey Mahogany-Rubber-Bee business gets> 1 feasible results and can be continuedPenelitian ini bertujuan Menganalisis finansial dan kelayakan hutan rakyat pola silvopastura dan apikultur di desa telaga langsat kecamatan takisung kabupaten tanah laut. Objek penelitian ini antaa lain Kelompok Tani pada hutan rakyat di desa Telaga Langsat. Data yang dikumpulkan berupa data primer dan data skunder. Data primer merupakan data yang bersumber langsung dari petani hutan rakyat, melalui teknik wawancara terstruktur (menggunakan kuisioner). Data sekunder merupakan data yang diambil dengan mengumpulkan informasi data yang sudah ada dengan meninta data penunjang ke kantor Desa serta berbagai sumber atau instansi. Hasil yang diperoleh dari penlitian menunjukan bahwa Analisis finansial Hutan Rakyat dengan Pola Silvopastura dan Apikultur layak untuk dilanjutkan dan kembangkan. Hasil perhitungan nilai NPV, IRR dan BCR dapat dipertimbangkan sesuai dengan finansial. Hasil perbandingan studi kelayakan finansial antara pengelolaan hutan rakyat pola silvopastura Mahoni-Karet-sapi menghasilkan nilai keuntungan paling besar dibandingkan pola Apikultur Mahoni-Karet-Lebah Madu. Dengan Nilai kentungan atau NVP 6.919.374.000 /ha, Nilai BCR 1,11 dan IRR sebesar 14%. Kelayakan pada Hutan Rakyat Mahoni-Karet-Sapi dan Mahoni-Karet-Lebah madu menggunakan Benefit Cost Ratio (BCR), terlihat bahwa Pola silvopastura Mahoni-Karet-Sapi dan apikultur Mahoni- Karet-Lebah Madu tersebut layak dan dapat dilanjutkan. Usaha Mahoni-Karet-Sapi mendapatkan hasil BCR>1 dan hasil usaha Mahoni-Karet-Lebah Madu mendapatkan hasil >1 layak dan dapat dilanjutkan